Dimensi kualitas hubungan dalam konteks jasa salon rambut - Aritonang, Lerbin R (Jurnal Manajemen, 2009)
It is generally accepted that relationship quality consists of three dimensions, i.e. satisfaction, trust, and commitment but there is no research about relationship between the dimensions. Data were gathered from 267 consumers of saloon service in 7 locations. The findings suggest that satisfaction is a positive predictor of trust. Satisfaction is a positive predictor of commitment. Trust is a positive predictor of commitment. Satisfaction is a direct predictor of commitment or an indirect predictor of commitment via trust.